Tribology Characteristics Of 22MNB5 Boron Steel Coated With Titanium Aluminum Nitrade - Abu Bakar, Muhammad Faizal (2019)
Boron steels are used in hot stamping process due to their good mechanical properties. During the stamping process, the dies are exposed to aggressive conditions including adhesive wear, thermal stresses, fatigue, and abrasion. In the present work, there are four samples with different HRC. The name for the four sample are first blank sample, blank sample with self-hardening, factory sample with 60 HRC and factory sample with 70 HRC. Blank sample is without doing anything. One sample will use different procedure of preparation which is using quenching that self-hardening while other two used hot stamping. Then all samples are coated with Titanium Alumiunm Nitrade (TiAlN) using Physical Vapor Deposition. After that, the samples coating were characterized and tested using Scanning Electron Microscopy (SEM), density, hardness test and wear test. By using SEM, the width of the stroke becomes smaller when using hot stamping process. For the hardness test, the sample form Proton Factory 70HRC stronger than others because using hot stamping process. Wear resistance of coatings increase due to the decreasing of coefficient of friction obtained. While others suggest that the transformation of the layer into produce martensite phase and more harder is the ultimate responsible for such changes. These four samples will make a comparison and find the best. Sample Proton Factory 70HRC it has lowest presence of porosity inside the sample so, the sample has highest hardness. The best will go further to machining process. The results in term of hardness and wear which are using hot stamping with higher HRC of sample will be better than others.